THE IMPORTANCE OF LIFE STORIES TO FOCUS STUDENTS’ATTENTION IN PRIMARY SCHOOL - N.Ismoilova; N.Malikova (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article deals with using a variety of life stories and multimedia tools to engage primary school students in their lessons.